SPEECH TACTICS IN MASS MEDIA DISCOURSE - Kaptiurova, Olena (Proceedings of National Aviation University (archive), 2014)
The article deals with the basic speech tactics used in mass media discourse. It has been stated that such tactics as contact establishment and speech interaction termination, yielding up initiative or its preserving are compulsory for the communicative situation of a talk show. Language personalities of television talk shows anchors and linguistic ways of the interview organisation are stressed. The material is amply illustrated with relevant examples.